Multistage-structure phenolic resin material, multistage-structure carbon material and preparation method of multistage-structure phenolic resin material and multistage-structure carbon material

By performing multi-order dynamic assembly of phenolic resin materials at the water-oil emulsion interface, the complex problem of multi-stage structural polymer preparation in the prior art is solved, and efficient assembly of submicron/micron-level multihedral structures and mesoporous channels is achieved. , phenolic resin and carbon materials with multi-layer structure and good dispersion were prepared.

CN119490632APending Publication Date: 2025-02-21DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202311038031.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-16
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The preparation strategies of existing multi-stage structural polymers are complex and cumbersome, making it difficult to achieve efficient assembly of submicron/micron-scale polyhedral structures and mesoporous channels of a single component polymer.

Method used

By performing multi-order dynamic assembly of phenolic resin materials at the water-oil emulsion interface, using reasonable control of covalent bonds and intermolecular interactions, precise control of the number of material assembly units, multi-level structure and pore size is achieved.

Benefits of technology

The phenolic resin material with submicron/micron-level polyhedral structure and its derived carbon material were successfully prepared. The material contains a polyhedral structure cavity inside, has mesoporous channels on the surface, and has good dispersion. It is suitable for a variety of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490632A_ABST
    Figure CN119490632A_ABST
Patent Text Reader

Abstract

The invention discloses a multilevel-structure phenolic resin material, a multilevel-structure carbon material and a preparation method, and the preparation method comprises the following steps: (1) mixing a mixture containing a surfactant, a cosurfactant, an organic solvent and water to obtain spherical emulsion droplets; and (2) adding a phenolic resin precursor and ammonia water into the spherical emulsion liquid drops, reacting, centrifuging, washing with alcohol, and drying to obtain the phenolic resin material with the multilevel structure. According to the preparation method, spherical emulsion droplets are used as soft templates, the phenolic resin material with the multilevel structure is synthesized in a one-pot liquid phase through multilevel sequential dynamic assembly on a water-oil interface, and the derivative carbon material subjected to heat treatment also maintains the original multilevel structure and morphology, is good in dispersity and has an adjustable polyhedral structure, an adjustable opening degree and an adjustable pore size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a multi-level structure phenolic resin material and a multi-level structure carbon material and a preparation method thereof, belonging to the technical field of material preparation. Background Art

[0002] As a kind of "soft matter", amorphous polymers tend to be spherical spontaneously under equilibrium conditions due to their long-range disordered structure. It is attractive to modify the microstructure of polymers. On the basis of retaining the original rich functional groups, the structural regulation of polymer micro / nanoparticles can optimize their physicochemical properties, such as mechanical stability, light absorption, adhesion, biocompatibility, etc., thereby expanding the application range of polymers. Rational design of polymer micro-nanostructures will also help to understand and build future bionic systems.

[0003] Organisms in nature, such as proteins, rely on unique multi-level structures (primary amino acid sequence, secondary peptide chain, tertiary spatial conformation, quaternary oligomers) to play a variety of functions. In recent years, researchers have been committed to developing polymers with multi-level structures, relying on interaction forces of different strengths and ranges to sequentially construct and assemble to form multiple continuous and different structural levels. However, most of the multi-level structured polymers currently developed rely on the composites between different polymer components, and the morphology is mainly block-based, non-micro-nano monodisperse particles, and the shape is irregular. There are few studies on the construction of multi-level structures of single-component polymers, and the existing preparation strategies are complex and cumbersome, requiring multi-step processes such as polymerization, modification, etching and other steps. The bottom-up chemical synthesis of micro-nanoscale polyhedral assembly polymers is unprecedented and extremely challenging. Summary of the invention

[0004] The purpose of the present application is to provide a multi-level structure of phenolic resin and derived carbon material and a preparation method thereof. The obtained multi-level structure phenolic resin material exhibits an overall morphology of submicron / micron-level assembled polyhedrons, breaking through the limitation that the existing amorphous phenolic resin material is spontaneously spherical or blocky, and contains a polyhedral structure cavity inside and has mesoporous channels on the surface. The carbonized derived carbon material maintains the original multi-level structure and morphology and has good dispersibility. The preparation method performs multi-level sequential dynamic assembly of phenolic resin materials at the interface of water-oil emulsion by rationally controlling covalent bonds and intermolecular interactions, and can achieve precise control of the number of material assembly units, multi-level structure and pore size.

[0005] According to the first aspect of the present application, a multi-level structure phenolic resin material is provided, wherein the interior of the phenolic resin material is a hollow structure, the cavity size is 0.2 to 8.0 um, and the cavity structure is at least one of a disc-shaped body, a triangle body, and a polyhedron;

[0006] The morphology of the phenolic resin material is selected from at least one of a dumbbell, a triangle, a regular tetrahedron, a cube, a regular octahedron, a regular dodecahedron, and a regular icosahedron;

[0007] The particle size of the phenolic resin material is submicron or micron.

[0008] Optionally, the particle size of the phenolic resin material is 0.5 to 10.0 um.

[0009] Optionally, the particle size of the phenolic resin material is selected from any value of 0.5um, 1um, 5um, 7um, 10um or a range between any two of the above values.

[0010] Optionally, the phenolic resin material is in-situ assembled from assembly units containing a pore structure.

[0011] Optionally, the phenolic resin material is in-situ assembled from 2 to 30 assembly units containing a porous structure.

[0012] Optionally, the pore structure of the assembly unit containing a pore structure is mesopore, and the pore diameter is 2 to 50 nm.

[0013] Optionally, the phenolic resin material has a three-layer structure, and the three-layer structure is assembled from secondary assembly monomers containing a primary pore structure.

[0014] Optionally, the phenolic resin material is a phenolic resin bulk polymer or a phenolic resin-based composite material with phenolic resin as a main component.

[0015] Optionally, the derived carbon material is obtained by pyrolysis of a phenolic resin material as a precursor, and retains the multi-level structure and morphology of the phenolic resin.

[0016] Optionally, the assembly is assembled from 2 to 30 monomers, and each monomer is regarded as a particle. The assembly can be in the shape of a dumbbell, a triangle, a polyhedron such as a regular tetrahedron, a cube, a regular octahedron, a regular dodecahedron, a regular icosahedron or other polyhedrons.

[0017] Optionally, the interior of the assembly is a hollow structure with a cavity size of 0.2 to 8.0 μm, and the cavity structure correspondingly exhibits a disc-shaped, triangular or polyhedral morphology.

[0018] Optionally, the morphology of the assembly unit containing the pore structure is selected from at least one of a spherical cap shape, a gyro shape, a cone shape, a crescent shape, a disc shape, a jellyfish shape, and a lotus shape.

[0019] Optionally, the secondary structure of the phenolic resin and the derived carbon material is an assembled monomer.

[0020] Optionally, the Feret assembly unit containing the pore structure max 0.3~3.0um, Feret min 0.05~2.0um.

[0021] Optionally, the secondary assembly monomer Feret max Any value selected from 0.3um, 0.5um, 1um, 1.5um, 2um, 2.5um, 3um or a range between any two of the above values.

[0022] Optionally, the secondary assembly monomer Feret min Any value selected from 0.05um, 0.1um, 0.5um, 1um, 1.5um, 2um or a range between any two of the above values.

[0023] Optionally, the channel arrangement of the mesopores is selected from at least one of face-centered cubic, body-centered cubic, two-dimensional cubic, and worm-like stacking.

[0024] Optionally, the pore structure is located inside and / or on the surface of each assembled monomer.

[0025] Optionally, the pore structure is mesoporous with a pore diameter of 2 to 50 nm, and the arrangement of the mesoporous channels includes face-centered cubic, body-centered cubic, two-dimensional hexagonal, worm-like stacking, and the like.

[0026] According to a second aspect of the present application, a method for preparing the multi-level structure phenolic resin material described above is provided, the preparation method comprising the following steps:

[0027] (1) mixing a mixture containing a surfactant, a co-surfactant, an organic solvent and water to obtain spherical emulsion droplets;

[0028] (2) adding a phenolic resin precursor and ammonia water into the spherical emulsion droplets, reacting, centrifuging, washing with alcohol, and drying to obtain the multi-level structure phenolic resin material.

[0029] Optionally, in step (1), the diameter of the spherical emulsion droplets is 0.2 to 8.0 um.

[0030] Optionally, the diameter of the spherical emulsion droplets is selected from any value of 0.2um, 0.3um, 0.5um, 1um, 2um, 4um, 5um, 6um, 8um or a range between any two of the above.

[0031] Optionally, in step (2), the phenolic resin precursor comprises a phenolic compound and an aldehyde compound, and the molar ratio of the phenolic compound to the aldehyde compound is 0.1 to 2:1.

[0032] Optionally, the molar ratio of the phenolic compound to the aldehyde compound is any value of 0.1:1, 0.3:1, 0.5:1, 1:1, 1.2:1, 1.5:1, 1.7:1, 2:1, or a range between any two of the above.

[0033] Optionally, the phenolic compound is selected from at least one of phenol, resorcinol, phloroglucinol, aminophenol, nitrophenol and halogenated phenol.

[0034] Optionally, the aldehyde compound is selected from at least one of formaldehyde, benzaldehyde, acetaldehyde, n-butyraldehyde, valeraldehyde and furfural.

[0035] Optionally, in step (2), the reaction temperature is 2 to 50° C., and the reaction time is 0.1 to 24 h.

[0036] Optionally, the reaction temperature is selected from any value of 2°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 50°C or a range between any two of the above values.

[0037] Optionally, the reaction time is selected from any value of 0.1h, 1h, 5h, 10h, 12h, 15h, 20h, 24h or a range between any two of the above.

[0038] Optionally, in step (1), the surfactant is selected from at least one of a cationic surfactant, an anionic surfactant, a nonionic surfactant, and an amphiphilic block copolymer.

[0039] Optionally, the surfactant is selected from at least one of cetyltrimethylammonium bromide, polyvinyl pyrrolidone, polyoxyethylene ether, Pluronic F127, and Pluronic F108.

[0040] Optionally, the concentration of the surfactant is 2 to 20 g / L.

[0041] Optionally, the co-surfactant is selected from at least one of ethanol, methanol, isopropanol, n-butanol and butanediol.

[0042] Optionally, the co-surfactant is ethanol.

[0043] Optionally, the volume ratio of the ethanol to water is 0.5 to 2:1.

[0044] Optionally, the organic solvent is selected from at least one of n-hexane, cyclohexane, toluene, m-xylene, p-xylene, mesitylene and nitrobenzene.

[0045] Optionally, the organic solvent is selected from at least one of alkane or aromatic hydrocarbon organic reagents such as n-hexane, cyclohexane, toluene, m-xylene, p-xylene, mesitylene, and nitrobenzene.

[0046] Optionally, the volume ratio of the organic solvent to water is 0.01-0.3:1.

[0047] Optionally, the molar ratio of the surfactant to the phenolic resin precursor is 0.001 to 0.01:1.

[0048] Optionally, the volume ratio of the ammonia water to the spherical emulsion droplets is 0.005 to 0.1:1.

[0049] Optionally, the centrifugal force of the centrifugation is 500-2000g.

[0050] Optionally, in step (2), the drying temperature is 30 to 100° C., and the drying time is 6 to 24 hours.

[0051] Optionally, in step (2), the alcohol in the alcohol washing is selected from at least one of ethanol and methanol.

[0052] According to a third aspect of the present application, a multi-level structure carbon material is provided, wherein the multi-level structure carbon material has a multi-level structure and morphology of a multi-level structure phenolic resin material;

[0053] The multi-level structure phenolic resin material is selected from the multi-level structure phenolic resin material described above.

[0054] According to a fourth aspect of the present application, a method for preparing the multi-level structure carbon material described above is provided, the preparation method comprising:

[0055] The multi-level structure phenolic resin material is carbonized under an inert atmosphere to obtain the multi-level structure carbon material.

[0056] Optionally, the inert atmosphere is selected from at least one of nitrogen, helium and argon.

[0057] Optionally, the carbonization temperature is 250-1000° C., and the carbonization time is 2-12 hours.

[0058] Optionally, the carbonization temperature is selected from any value of 250°C, 300°C, 500°C, 600°C, 800°C, 1000°C or a range between any two of the above values.

[0059] Optionally, the carbonization time is selected from any value among 2h, 4h, 6h, 8h, 10h, 12h or a range between any two of the above.

[0060] In the present application, the preparation method of the multi-level structured phenolic resin and derived carbon material comprises the following steps:

[0061] (1) ultrasonically mixing a surfactant, a co-surfactant, water and an organic phase to obtain spherical emulsion droplets;

[0062] (2) adding a phenolic resin precursor and ammonia water to the emulsion in sequence, reacting at a certain temperature for a period of time, collecting the material by differential centrifugation, repeatedly washing with ethanol for several times, and drying to obtain the phenolic resin material with the multi-level structure.

[0063] (3) Carbonizing the phenolic resin material with a multi-level structure at a high temperature under an inert atmosphere to obtain the carbon material with a multi-level structure.

[0064] The beneficial effects of this application include:

[0065] 1) The multi-level structure of phenolic resin and derived carbon materials provided in the present application exhibits submicron / micron-scale anisotropic assembly structures including dumbbell, triangle or polyhedral morphologies, etc., and contains special structural cavities inside and mesoporous channels on the surface.

[0066] 2) The preparation method of the multi-level structured phenolic resin and derived carbon material provided in this application improves the traditional spherical morphology of phenolic resin. The bottom-up multi-level assembly strategy is used to achieve island nucleation and growth of phenolic resin on the surface of emulsion droplets, and further dynamically assemble under the drive of the lowest thermodynamic free energy to form the final special multi-level structure assembly.

[0067] 3) The preparation method of the multi-level structured phenolic resin and derived carbon material provided in this application has a simple preparation technology, and the composition and structure of the material are easy to control. By precisely controlling the emulsion droplet size, reaction temperature and the type of phenolic resin precursor, the composition of the material, the number of assembled monomers, the multi-level structure and the pore size can be easily changed to meet the needs of different applications.

[0068] 4) The present application uses spherical emulsion droplets as soft templates, dynamically assembles in a multi-level order at the water-oil interface, and synthesizes a phenolic resin material with a multi-level structure in a one-pot liquid phase. The derived carbon material after heat treatment also maintains the original multi-level structure and morphology, has good dispersibility, and has an adjustable polyhedral structure, degree of openness and pore size. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] Figure 1 (a) 500nm scanning electron microscope image and (b) 500nm transmission electron microscope image of the multi-level structure phenolic resin material prepared under the conditions of Example 1 of the present invention.

[0070] Figure 2This is a pore size distribution diagram of a multi-level phenolic resin material prepared under the conditions of Example 1 of the present invention.

[0071] Figure 3 (a) 500nm scanning electron microscope image and (b) 500nm transmission electron microscope image of the multi-level structure phenolic resin-based composite material prepared under the conditions of Example 2 of the present invention.

[0072] Figure 4 This is a 500nm transmission electron microscope image of a multi-level phenolic resin material prepared under the conditions of Example 3 of the present invention.

[0073] Figure 5 This is a 200nm transmission electron microscope image of the multi-level structured derivative carbon material prepared under the conditions of Example 4 of the present invention.

[0074] Figure 6 This is a 200nm transmission electron microscope image of a multi-level phenolic resin material prepared under the conditions of Example 5 of the present invention.

[0075] Figure 7 This is a 100 nm scanning electron microscope image of a multi-level phenolic resin material prepared under the conditions of Example 6 of the present invention.

[0076] Figure 8 This is a 1.0 um transmission electron microscope image of a multi-level phenolic resin material prepared under the conditions of Example 7 of the present invention.

[0077] Fig. 9 This is a 500nm transmission electron microscope image of a multi-level phenolic resin material prepared under the conditions of Example 8 of the present invention.

[0078] Fig.10 This is a 2.0 um transmission electron microscope image of the phenolic resin material prepared under the conditions of Comparative Example 1 of the present invention.

[0079] Fig.11 This is a 200nm transmission electron microscope image of the phenolic resin material prepared under the conditions of Comparative Example 2 of the present invention.

[0080] Fig.12 This is a 2.0 um transmission electron microscope image of the phenolic resin material prepared under the conditions of Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0081] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0082] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0083] The analysis method in the examples of this application is as follows:

[0084] The scanning electron microscope images were obtained using JSM-7900F from JEOL Ltd. at an accelerating voltage of 3 kV.

[0085] Transmission electron microscope images were obtained using Hitachi 7700 from Hitachi, Japan, at an accelerating voltage of 100 kV;

[0086] The nitrogen adsorption test was carried out using the ASAP2460 multifunctional adsorption instrument produced by Micromeritics Corporation of the United States to obtain the pore size distribution diagram.

[0087] Example 1

[0088] Weigh 0.5g F127 and dissolve it in 25mL water and 25mL ethanol to form a solution. Add 1.0mL 1,3,5-trimethylbenzene and obtain an emulsion with a diameter of 1.4um after ultrasonication. Add 0.25g aminophenol, 0.25mL ammonia water and 0.35mL formaldehyde aqueous solution in sequence, stir at 30℃ for 12 hours, centrifuge the product under the action of 900g centrifugal force and wash it three times with ethanol, and then dry it to obtain a phenolic resin material with a multi-level structure.

[0089] Figure 1 The scanning electron microscope image and transmission electron microscope image of the multi-level phenolic resin material prepared under the conditions of Example 1 of the present invention are shown. Figure 1 It can be seen that the material is an assembly composed of 12 spherical cap monomers, forming a regular icosahedron morphology. The maximum cross-sectional diameter of the spherical cap monomer is 0.82μm and the height is 0.22μm. The internal cavity is a regular dodecahedron structure, and the surface of the material has ordered mesoporous channels.

[0090] Figure 2 This is a pore size distribution diagram of the multi-level phenolic resin material prepared under the conditions of Example 1 of the present invention. Figure 2 It can be seen that the material has mesoporous channels of about 5.3 nm.

[0091] Example 2

[0092] Weigh 0.8g F127 and dissolve it in 40mL water and 40mL ethanol to form a solution. Add 1.6mL 1,3,5-trimethylbenzene and obtain an emulsion with a diameter of 1.2um after ultrasonication. Add 0.4g aminophenol, 0.4g dopamine, 0.8mL ammonia water and 0.56mL formaldehyde aqueous solution in sequence, stir at 30℃ for 24 hours, centrifuge the product under the action of 1200g centrifugal force and wash it three times with ethanol, and then dry it to obtain a multi-level structure phenolic resin-based composite material.

[0093] Figure 3The scanning electron microscope image and transmission electron microscope image of the multi-level phenolic resin-based composite material prepared under the conditions of Example 2 of the present invention are shown. Figure 3 It can be seen that the material is an assembly composed of three spherical cap monomers, forming an equilateral triangle morphology. The maximum cross-sectional diameter of the spherical cap monomer is 1.1μm and the height is 0.65μm. The internal cavity also shows a triangular structure, and the surface of the material has mesoporous channels.

[0094] Example 3

[0095] Weigh 0.3g Brij TM C20 was dissolved in 11 mL of water and 11 mL of ethanol to form a solution. 1.0 mL of 1,3,5-trimethylbenzene was added, and an emulsion with a diameter of 1.8 μm was obtained after ultrasonication. 0.15 g of aminophenol, 0.2 mL of ammonia water and 0.2 mL of formaldehyde aqueous solution were added in sequence, stirred at 30°C for 12 hours, the product was centrifuged out under the action of 1000 g centrifugal force and washed three times with ethanol, and a multi-level phenolic resin material was obtained after drying.

[0096] Figure 4 This is a transmission electron microscope image of a phenolic resin material with a multi-level structure prepared under the conditions of Example 3 of the present invention. Figure 4 It can be seen that the material is an assembly composed of two spherical cap monomers, forming a dumbbell-shaped morphology. The maximum cross-sectional diameter of the spherical cap monomer is 1.68 μm and the height is 1.01 μm. The internal cavity is correspondingly a disc-shaped structure.

[0097] Example 4

[0098] Weigh 0.05g F127 and dissolve it in 5mL water and 5mL ethanol to form a solution. Add 0.15mL 1,3,5-trimethylbenzene and obtain an emulsion with a diameter of 0.8um after ultrasonication. Add 0.2g aminophenol, 0.1mL ammonia water and 0.2mL formaldehyde aqueous solution in sequence, stir at 30℃ for 1 hour, centrifuge the product under the action of 2000g centrifugal force and wash it three times with ethanol, dry it, put it in a tubular furnace and bake it at 700℃ for 3 hours under nitrogen atmosphere to obtain a multi-level structured derived carbon material.

[0099] Figure 5 This is a transmission electron microscope image of a multi-level structured derivative carbon material prepared under the conditions of Example 4 of the present invention. Figure 5 It can be seen that the material maintains the structural morphology of the polyhedral assembly after calcination.

[0100] Example 5

[0101] Weigh 0.25g F127 and dissolve it in 50mL water and 50mL ethanol to form a solution. Add 5.0mL p-xylene and obtain an emulsion with a diameter of 1.0um after ultrasonication. Add 0.5g aminophenol, 0.5mL ammonia water and 0.7mL formaldehyde aqueous solution in sequence, stir at 30℃ for 24 hours, centrifuge the product under the action of 1100g centrifugal force and wash it three times with ethanol, and then dry it to obtain a phenolic resin material with a multi-level structure.

[0102] Figure 6 This is a transmission electron microscope image of a phenolic resin material with a multi-level structure prepared under the conditions of Example 5 of the present invention. Figure 6 It can be seen that the material is an assembly composed of 6 gyro-shaped monomers, forming a cubic morphology. The maximum cross-sectional diameter of the gyro-shaped monomer is 0.87μm and the height is 0.28μm. The internal cavity is a multi-faceted three-dimensional structure with ordered mesoporous channels on the surface.

[0103] Example 6

[0104] Weigh 0.08g F127 and dissolve it in 16mL water and 14mL ethanol to form a solution. Add 1.6mL toluene and obtain an emulsion with a diameter of 1.0um after ultrasonication. Add 0.16g aminophenol, 0.2mL ammonia water and 0.25mL formaldehyde aqueous solution in sequence, stir at 30℃ for 2 hours, centrifuge the product under the action of 1000g centrifugal force and wash it three times with ethanol, and then dry it to obtain a phenolic resin material with a multi-level structure.

[0105] Figure 7 This is a scanning electron microscope image of a phenolic resin material with a multi-level structure prepared under the conditions of Example 6 of the present invention. Figure 7 It can be seen that the material is an assembly of 5 conical monomers, forming an open hollow cube morphology. The maximum cross-sectional diameter of the conical monomer is 0.56 μm, the height is 0.20 μm, and there are mesoporous channels on the surface.

[0106] Example 7

[0107] Weigh 0.4g F127 and dissolve it in 22mL water and 25mL ethanol to form a solution. Add 0.4mL 1,3,5-trimethylbenzene and obtain an emulsion with a diameter of 1.6um after ultrasonication. Add 0.2g aminophenol, 0.3mL ammonia water and 0.28mL formaldehyde aqueous solution in sequence, stir at 10℃ for 18 hours, centrifuge the product under the action of 2000g centrifugal force and wash it three times with ethanol, and then dry it to obtain a phenolic resin material with a multi-level structure.

[0108] Figure 8 This is a transmission electron microscope image of a phenolic resin material with a multi-level structure prepared under the conditions of Example 7 of the present invention. Figure 8It can be seen that the material is a hollow polyhedral assembly composed of multiple crescent-shaped monomers.

[0109] Example 8

[0110] Weigh 0.5g F127 and dissolve it in 30mL water and 30mL ethanol to form a solution. Add 0.7mL 1,3,5-trimethylbenzene and obtain an emulsion with a diameter of 1.4um after ultrasonication. Add 0.15g aminophenol, 0.2mL ammonia water and 0.2mL formaldehyde aqueous solution in sequence, stir at 30℃ for 0.2 hours, centrifuge the product under the action of 4000g centrifugal force and wash it three times with ethanol, and then dry it to obtain a multi-level phenolic resin material.

[0111] Fig. 9 This is a transmission electron microscope image of a phenolic resin material with a multi-level structure prepared under the conditions of Example 8 of the present invention. Fig. 9 It can be seen that the material is a hollow polyhedral assembly composed of multiple thin disc monomers. The maximum cross-sectional diameter of the disc-shaped monomer is 0.35μm, the height is 0.06μm, and there are ordered mesoporous channels on the surface.

[0112] Comparative Example 1

[0113] Weigh 0.2g F127 and dissolve it in 20mL ethanol to form a solution. Add 0.4mL 1,3,5-trimethylbenzene and obtain a clear and transparent solution after ultrasonic treatment. Add 0.1g aminophenol, 0.1mL ammonia water and 0.14mL formaldehyde aqueous solution in sequence, stir at 30℃ for 12 hours, centrifuge the product under the action of 5000g centrifugal force and wash it three times with ethanol, and then dry it to obtain the phenolic resin material.

[0114] Fig.10 This is a transmission electron microscope image of the phenolic resin material prepared under the conditions of comparative example 1 of the present invention. Fig.10 It can be seen that the material appears as agglomerated spherical solid particles without the formation of a multi-level structure.

[0115] Comparative Example 2

[0116] Weigh 1.0g F127 and dissolve it in 10mL water and 10mL ethanol to form a solution. Add 0.4mL 1,3,5-trimethylbenzene and obtain an emulsion with a diameter of 0.02um after ultrasonication. Add 0.1g aminophenol, 0.1mL ammonia water and 0.14mL formaldehyde aqueous solution in sequence, stir at 30℃ for 12 hours, centrifuge the product under the action of 5000g centrifugal force and wash it three times with ethanol, and then dry it to obtain the phenolic resin material.

[0117] Fig.11 This is a transmission electron microscope image of the phenolic resin material prepared under the conditions of Comparative Example 2 of the present invention. Fig.11 It can be seen that the material behaves as mesoporous spheres.

[0118] Comparative Example 3

[0119] Weigh 0.3g F127 and dissolve it in 14mL water and 14mL ethanol to form a solution. Add 0.5mL 1,3,5-trimethylbenzene and obtain an emulsion with a diameter of 1.5um after ultrasonication. Add 0.1g aminophenol and 0.14mL formaldehyde aqueous solution in sequence, stir at 30℃ for 12 hours, centrifuge the product under the action of 1000g centrifugal force and wash it three times with ethanol, and then dry it to obtain the phenolic resin material.

[0120] Fig.12 This is a transmission electron microscope image of the phenolic resin material prepared under the conditions of comparative example 3 of the present invention. Fig.12 It can be seen that the material exhibits a collapsed and shrunk hollow structure.

[0121] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A multi-level phenolic resin material, characterized in that: The interior of the phenolic resin material is a hollow structure, the cavity size is 0.2 to 8.0 um, and the cavity structure is at least one of a disc, a triangle, and a polyhedron; The morphology of the phenolic resin material is selected from at least one of a dumbbell, a triangle, a regular tetrahedron, a cube, a regular octahedron, a regular dodecahedron, and a regular icosahedron; The particle size of the phenolic resin material is submicron or micron.

2. The multi-level structure phenolic resin material according to claim 1, characterized in that: The particle size of the phenolic resin material is 0.5 to 10.0 um; Preferably, the phenolic resin material is in-situ assembled from assembly units containing a pore structure; Preferably, the phenolic resin material is in-situ assembled from 2 to 30 assembly units containing a porous structure.

3. The multi-level structure phenolic resin material according to claim 2, characterized in that: The morphology of the assembly unit containing the hole structure is selected from at least one of a spherical cap shape, a gyro shape, a cone shape, a crescent shape, a disc shape, a jellyfish shape, and a lotus shape; Preferably, the Feret assembly unit containing the pore structure max 0.3~3.0um, Feret min 0.05~2.0um; Preferably, the pore structure inside or on the surface of the assembly unit containing a pore structure is mesopore, and the pore diameter is 2 to 50 nm.

4. The multi-level structure phenolic resin material according to claim 2, characterized in that: The channel arrangement of the mesopores is selected from at least one of face-centered cubic, body-centered cubic, two-dimensional cubic, and worm-like stacking.

5. The method for preparing the multi-stage phenolic resin material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) mixing a mixture containing a surfactant, a co-surfactant, an organic solvent and water to obtain spherical emulsion droplets; (2) adding a phenolic resin precursor and ammonia water into the spherical emulsion droplets, reacting, centrifuging, washing with alcohol, and drying to obtain the multi-level structure phenolic resin material.

6. The preparation method according to claim 5, characterized in that: In the step (1), the diameter of the spherical emulsion droplets is 0.2 to 8.0 μm; Preferably, in step (2), the phenolic resin precursor comprises a phenolic compound and an aldehyde compound, and the molar ratio of the phenolic compound to the aldehyde compound is 0.1 to 2:1; Preferably, the phenolic compound is selected from at least one of phenol, resorcinol, phloroglucinol, aminophenol, nitrophenol, and halogenated phenol; Preferably, the aldehyde compound is selected from at least one of formaldehyde, benzaldehyde, acetaldehyde, n-butyraldehyde, valeraldehyde and furfural; Preferably, in step (2), the reaction temperature is 2 to 50° C., and the reaction time is 0.1 to 24 h.

7. The preparation method according to claim 5, characterized in that: In the step (1), the surfactant is selected from at least one of a cationic surfactant, an anionic surfactant, a nonionic surfactant, and an amphiphilic block copolymer; Preferably, the surfactant is selected from at least one of cetyltrimethylammonium bromide, polyvinyl pyrrolidone, polyoxyethylene ether, Pluronic F127, and Pluronic F108; Preferably, the concentration of the surfactant is 2 to 20 g / L; Preferably, the co-surfactant is selected from at least one of ethanol, methanol, isopropanol, n-butanol and butanediol; Preferably, the co-surfactant is ethanol; Preferably, the volume ratio of ethanol to water is 0.5 to 2:1; Preferably, the organic solvent is selected from at least one of n-hexane, cyclohexane, toluene, m-xylene, p-xylene, mesitylene, and nitrobenzene; Preferably, the volume ratio of the organic solvent to water is 0.01-0.3:

1.

8. The preparation method according to claim 5, characterized in that: The molar ratio of the surfactant to the phenolic resin precursor is 0.001 to 0.01:1; Preferably, the volume ratio of the ammonia water to the spherical emulsion in the spherical emulsion droplets is 0.005 to 0.1:1; Preferably, the centrifugal force of the centrifugation is 500 to 2000 g; Preferably, in step (2), the drying temperature is 30 to 100° C., and the drying time is 6 to 24 hours; Preferably, in step (2), the alcohol in the alcohol washing is selected from at least one of ethanol and methanol.

9. A multi-level structure carbon material, characterized in that: The multi-level structure carbon material has the multi-level structure and morphology of the multi-level structure phenolic resin material; The multi-stage structure phenolic resin material is selected from the multi-stage structure phenolic resin material according to any one of claims 1 to 4.

10. The method for preparing the multi-level structure carbon material according to claim 9, characterized in that: The preparation method comprises: In an inactive atmosphere, carbonizing the multi-level structure phenolic resin material to obtain the multi-level structure carbon material; Preferably, the inert atmosphere is selected from at least one of nitrogen, helium and argon; Preferably, the carbonization temperature is 250-1000° C., and the carbonization time is 2-12 hours.

Citation Information

Patent Citations

  • Carbon hollow sphere material with hierarchical porous structure and preparation method thereof

    CN103613085A

  • Preparation method of dozens-of-gram hierarchical pore mono-dispersed 200-300nm bowl-shaped carbon material

    CN105668541A

  • Bird nest-shaped polymer bowl, porous carbon bowl and preparation method and application thereof

    CN112778569A

  • Phenolic resin material as well as preparation method and application thereof

    CN112979896A

  • Phenolic resin microspheres, porous carbon material microspheres as well as preparation method and application of phenolic resin microspheres and porous carbon material microspheres

    CN115651143A

Cited By

  • Hollow spherical assembly polymer, carbon material as well as preparation method and application of hollow spherical assembly polymer and carbon material

    CN120248380A

  • Polymer with asymmetric structure, carbon microsphere and preparation method thereof

    CN120248381A

  • Asymmetric structure polymer, carbon microspheres and preparation method thereof

    CN120248381B

  • Directional preparation method and application of jellyfish-shaped polymer and carbon material

    CN121427040A